(untitled) (Medico Legal Update, 2020)
Monitoring of blood glucose levels is clinically crucial in managing diseases affecting insulin secretion and resistance, most notably diabetes mellitus and cystic fibrosis. Blood glucose s used to monitor the amount of glucose in the blood, especially patients with symptoms with the abnormally of high or low blood glucose levels. Most recently, they enable diabetic patients to administer appropriate insulin doses to human health. The availability of in-house glucometers, as opposed to clinical-use equipment, has dramatically improved the quality of life of diabetic’s patient. However, such monitors require a blood draw through finger pricks for each test, which causes pain and inconvenience. Each test also needs a new test-strip, contributing to the recurring cost of such a device. Typically the blood glucose monitoring is the non-invasive technique which may cause distress and discomfort, particularly in the pediatric patient. We introduce an architecture that uses Near Infrared (NIR) spectroscopy to determine blood glucose levels based on transmittance spectroscopy on the nose lobe. The Measurement of glucose in the respiratory fluid by a collection of exhaled breath in condensate and therefore, a potentially clinically useful method of estimating blood glucose levels identified and therefore it is the excellent agreement between these diabetics blood glucose level.